Development of technology for producing biodegradable hybrid composites based on polyethylene, starch, and monoglycerides - I. Yu. Vasilyev; V. V. Ananyev; V. V. Kolpakova; A. S. Sardzhveladze (Тонкие химические технологии)
Objectives. This work aimed to develop technology to produce biodegradable hybrid composite (BHC) films based on low-density polyethylene (LDPE) 115030-070 and thermoplastic starches (TPS) of various origins (corn, pea, and rice), with distilled monoglycerides as the plasticizer. The properties of the produced BHC films were studied and the optimal native starch : glycerol : monoglycerides ratio is proposed.Methods. TPS and BHC films based on this material were produced from different types of native starches in laboratory extruders (Brabender and MashPlast, Russia), and the extruded melts were subjected to ultrasonic vibrations. The structure and appearance of the BHC films were studied using scanning electron microscopy and rheology. Their biodegradability was assessed by immersing them in biocompost for three months. To evaluate the mechanical performance of the BHC films produced with and without ultrasound, the changes in tensile stress and elongation at break were determined during the biodegradation process.Results. The BHC films had a homogeneous structure, except small agglomerates (non-melted starch grains), which did not reduce their quality. The films with monoglycerides had high tensile strength, which was comparable with low-density polyethylene. After removing samples of the BHC films from the biocompost, their tensile strength decreased by 20%, which shows their biodegradability.Conclusions. The produced biodegradable composite films and the technology used to produce them will be applicable for the packaging industry to reduce environmental impact.